1998
DOI: 10.1302/0301-620x.80b1.7453
|View full text |Cite
|
Sign up to set email alerts
|

PCL reconstruction: In vitro biomechanical comparison of 'isometric' versus single and double-bundled 'anatomic' grafts

Abstract: We compared the ability of three different posterior cruciate ligament (PCL) reconstructions to restore normal anteroposterior laxity to the knee from 0 to 130 degrees of knee flexion. Cadaver knees were tested intact, after PCL rupture or after bone-patellar tendon-bone grafting. Grafts were performed isometrically or with a single bundle representing the anatomical anterior PCL fibre bulk (aPC) or with a double bundle that added the posterior PCL fibre bulk (pPC). The grafts were tensioned to restore normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
203
0
22

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 241 publications
(226 citation statements)
references
References 20 publications
1
203
0
22
Order By: Relevance
“…This ligament is clearly not an isometric structure, and so differs significantly from the ACL, and an isometric reconstruction would not fit in with the natural behaviour. This was shown by Race and Amis [40] who also, along with Harner et al [20] and Mannor et al [30], showed that a double-bundled PCL reconstruction re-established normal tibial posterior laxity significantly better than did singlebundled reconstructions. This work in vitro, however, has not yet led to reports of significant advantages in clinical results.…”
Section: Conclusion For the Surgeonmentioning
confidence: 71%
“…This ligament is clearly not an isometric structure, and so differs significantly from the ACL, and an isometric reconstruction would not fit in with the natural behaviour. This was shown by Race and Amis [40] who also, along with Harner et al [20] and Mannor et al [30], showed that a double-bundled PCL reconstruction re-established normal tibial posterior laxity significantly better than did singlebundled reconstructions. This work in vitro, however, has not yet led to reports of significant advantages in clinical results.…”
Section: Conclusion For the Surgeonmentioning
confidence: 71%
“…Several investigators reported that the tension of the 2 bundles is different with double-bundle PCL reconstruction, based on the angle of knee motion. 3,5,11,12 Nonanchorage of the graft on the femoral side theoretically allows the relative motion of the graft on the femur along with knee motion, and it can be expected to transfer the force from one graft to the other graft. We expected that it could even move the graft along with knee motion.…”
Section: Discussionmentioning
confidence: 99%
“…Os trabalhos biomecânicos recentes visam avaliar técnicas cirúrgicas e compará-las entre si. 1,5,7,10,12,13,17,19,20,22,23,24 . Neste estudo, o objetivo foi encontrar valor em milímetros para joelho normal e comparar os resultados com o joelho lesado.…”
Section: Discussionunclassified
“…Sua anatomia e arranjo espacial estão diretamente relacionados ao funcionamento, como elementos de restrição do movimento articular 4,8,9,14,15 . Embora os relatos tenham trazido muita informação a respeito do LCC, a causa de sua ruptura freqüentemente não é conhecida e o modo ideal de tratamento permanece controverso 12,13,21,22,23 . O mecanismo e extensão destas lesões dependem da magnitude e direção da força traumática e da posição da articulação, no momento da aplicação desta força 3,7,10,16,19,20 .…”
unclassified